2018
DOI: 10.1103/physrevapplied.9.014010
|View full text |Cite
|
Sign up to set email alerts
|

Physical Origin of Transient Negative Capacitance in a Ferroelectric Capacitor

Abstract: Transient negative differential capacitance (NC), the dynamic reversal of transient capacitance in an electrical circuit is of highly technological and scientific interest since it probes the foundation of ferroelectricity. In this letter, we study a resistor-ferroelectric capacitor (R-FeC) network through a series of coupled equations based on Kirchhoffs law, Electrostatics, and Landau theory. We show that transient NC in a R-FeC circuit originates from the mismatch between rate of free charge change on the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 25 publications
6
55
0
1
Order By: Relevance
“…The interpretation of the V ‐drop effect by the conventional FE switching model can be further supported by the disappearance of the effect during the subsequent switching cycles only up to ten times . Consistently, Chang et al showed that the mismatch in switching rate between the free charge on the metal plate and the bound charge in FE layer during the polarization switching is a physical origin of the V ‐drop effect in a ferroelectric capacitor …”
Section: Basic Concepts Of Nc From the Ferroelectric Thin Filmmentioning
confidence: 83%
“…The interpretation of the V ‐drop effect by the conventional FE switching model can be further supported by the disappearance of the effect during the subsequent switching cycles only up to ten times . Consistently, Chang et al showed that the mismatch in switching rate between the free charge on the metal plate and the bound charge in FE layer during the polarization switching is a physical origin of the V ‐drop effect in a ferroelectric capacitor …”
Section: Basic Concepts Of Nc From the Ferroelectric Thin Filmmentioning
confidence: 83%
“…[25,26] Subsequently, NC has been reported in many electronic devices, such as bilayer capacitors, [91,92] p-n junctions, [27,28] Schottky diodes, [29,30] metal-insulator-metal (MIM) devices, [31] polycrystalline solar cells, [32] quantum devices, [33,34] and superlattices. [93] Besides, time-resolved measure of NC is realized in 2018. Jonscher proposed that the right way for analyzing NC is through the time-domain behavior under step function bias, which involves an initial decrease in current followed by an increase over a period before finally decaying to zero.…”
Section: Negative Capacitancementioning
confidence: 99%
“…Our recent work theoretically proved that this differential negative capacitance is driven by the free charge-polarization mismatch as qualitatively pointed out in Ref. [6], which can be well described under Landau's mean field theory [7]. In 2018, the transient differential negative capacitance has been also experimentally observed in a FE MOS capacitor [8], indicating the existence of transient mismatch between bound charge and free charge in a MOS structure.…”
mentioning
confidence: 57%
“…Similar to Ref. [7], the physical origin of this transient SS can be understood by taking the time derivative of Eq. 3 as shown below.…”
mentioning
confidence: 87%
See 1 more Smart Citation